MODERN SOLUTIONS FOR CLEANING WASTEWATER FROM CAR WASHES - Feruza I. Salomova; Khosiyat A. Sadullayeva; Guzal Toshmatova (Central Asian Journal of Medicine, 2024)
The research conducted examined the ecological aspects of washing cars, the levels and characteristics of washing detergents used, and their impact on polluting natural waters. The results of disposing of wastewater generated from washing cars were presented. The necessity of using water recycling systems was identified and substantiated, along with aspects that need to be considered in their use.